Pendampingan Pendidikan Disiplin Karakter Pada Pembiasaan Shalat Dhuha Di Sekolah Dasar - Widi, Widi (Yayasan Darussalam Bengkulu, 2023)
Worship is one way to draw closer to Allah SWT. Worship has two main focuses: mahdhah worship and ghairu mahdhah worship. And one of the mahdhah worship is prayer, which in Arabic is also called